POLYMER FUNCTIONALIZATION FOR THE SUSPENSION OF CARBON NANOTUBES IN BULK POLYMER - Chadwick, Ryan C. (My University, 2014)
Carbon nanotubes have great strength, high conductivities, and very large aspect ratios. Their physical, mechanical, and electrical properties are unique and ideally suited for use in structural materials, nano-electronic devices, and as a conductive filler. The homogeneous incorporation of carbon nanotubes in bulk materials such as polymers is difficult to achieve. This is further complicated by the inhomogeneity of carbon nanotube samples. The desire to incorporate carbon nanotubes in a wide variety of devices has been the impetus for carbon nanotube chemistry over the last decade. This requires techniques for dispersal and processing, as well as methodologies for producing monodisperse samples. In Chapter 1, this thesis discusses the fundamental properties of carbon nanotubes and gives a brief overview of the state-of-the-art in carbon nanotube separation, dispersion, and the incorporation of carbon nanotubes in bulk polymers. Chapters 2, 3, and 4 outline our efforts in the area of bulk polymer suspensions; in polystyrene (Ch. 2) and in crosslinked polydimethylsiloxane elastomers (Ch. 3 and 4). Chapter 2 describes our efforts to gain an understanding of the factors limiting the graft density of polymers on the surface of carbon nanotubes, and our insights on the ability of polymer grafts to compatibilize carbon nanotubes with a host polymer. Chapter 3 discusses the application of the Piers-Rubinsztajn reaction as a method of functionalizing the surface of nanotubes with silanes, and crosslinking them within silicone rubbers. Chapter 4 outlines the development of a supramolecular strategy for the dispersion of carbon nanotubes within silicone elastomers using conjugated and di-block co-polymers. Lastly, Chapters 5 through 6 explore the initial stages of development of a “universal” polymer for the dispersion of carbon nanotubes based on highly reactive cyclooctyne monomer units (Ch. 5) and the precursor chemistry required to make this unit on sufficient scale (Ch. 6).
Keywords: Polymer Chemistry; Carbon Nanotubes